Methodological contribution of the metric studies of information for the analysis of interdisciplinarity in environmental sciences - Cavalcanti, Daniele Belmont de Farias; Leite, Breno Ricardo de Araújo; Farias, Gabriela Belmont de (Faculdade de Filosofia e Ciências, 2019)
Through a bibliographical survey, the article presents a reflection on the conceptual and theoretical aspects of interdisciplinarity and metric studies of information and its interrelation with the development of environmental sciences. It presents the emergence of environmental sciences, which was a response to the complexity of environmental problems, due to the indissociability between anthropic and natural systems, which are related to economic and social problems mediated by science and technology. These aspects brought to the area intrinsic interdisciplinary characteristics, which were portrayed in specific orientations to observe interdisciplinarity in graduate programs, but without the specification of how we could check these factors. This study presented that the metric studies of information could be indicative for the development of interdisciplinary indicators, thus the contribution of this article resided in presenting a methodological protocol and validation, aiming to generate indicators of analysis to understand interdisciplinarity in the postgraduate programs in the area of environmental sciences, based on the metric studies of information.